Through the town trace the trail - Shuttlewood, Craig (Templar Publishing, 2015)
RHYMING & WORDPLAY BOOKS. Trace the Trail: Through the Town is an exciting day out in town that you can follow with your finger! This interactive book for toddlers lets them explore the world by tracing a tactile pathway. Each spread will feature a vehicle on its way through the city travelling through ups and downs and contrasts. A train will over the bridge and under the ground, a car will go up and down the street. Craig Shuttlewood's bold illustrations make this a dynamic and graphic cityscape. Ages 0+
On board pages
Keywords: City and town life / Juvenile fiction; Trails / Juvenile fiction; Board books; City and town life; Trails; Fiction; Juvenile works; Textured books; Toy and movable books; Bilderbuch